Type of Refugee Accommodation and Health of Residents: A Cross-Sectional, Population-Based Cluster Analysis in South-West Germany - Amir Mohsenpour; Verena Dudek; Kayvan Bozorgmehr; Kayvan Bozorgmehr; Louise Biddle; Oliver Razum; Odile Sauzet; Odile Sauzet (Frontiers Media S.A., 2023)
Objectives: Few studies have assessed whether refugees' health is associated with accommodation characteristics. We aimed to devise a typology of refugee accommodation based on variables on the accommodation and its physical context before assessing its association with health in multivariate analyses.Methods: We performed a cluster analysis based on a hierarchal, agglomerative clustering algorithm using Euclidean Distance and Ward's method. We analysed accommodation clusters based on number of inhabitants, degree of housing deterioration, urbanity of location (urban/rural distinction), and remoteness (walking distance to shops, medical or administrative services). In total, we analysed health and accommodation data of 412 refugees and asylum seekers from 58 different accommodation facilities in the federal state of Baden-Württemberg in the south-west of Germany.Results: Accommodations with a moderate occupation, lowest levels of deterioration, and a central urban location showed the best health outcomes in terms of subjective general health status, depression, and generalized anxiety disorder (GAD). Associations were strongest for GAD and weakest for depression.Conclusion: Our findings inform policymakers on layout and location of refugee collective accommodation centres.